Women Named by Others: A Study of the Late-Medieval Anthroponymic System from a Gender Perspective - Bouzas, Paula (Madrygal. Revista de Estudios Gallegos, 2024)
The study of two 15th century documentary collections brings to light divergences in the naming system by gender. When the data are disaggregated from this perspective, considering female and male anthroponymic sequences separately, particularities emerge regarding the type of chain and differences in the distribution, presence, and nature of second-name types. In some cases these are trends that, because they pertain to a group with a minority presence in the sources, remain imperceptible in the overall dataset. In this contribution we delve into these divergences and present numerous examples. This work aims to contribute to the study of the late-medieval Galician anthroponymic system and to provide new data for understanding its evolution.